Quantitative Assessment of Parenchymal Involvement Using 3D Lung Model in Adolescent With Covid-19 Interstitial Pneumonia - Borro, Luca; Ciliberti, Paolo; Santangelo, Teresa Pia; Magistrelli, Andrea; Campana, Andrea; Carducci, Francesca Calò; Caterina, Marabotto; Tomà, Paolo; Secinaro, Aurelio (Frontiers in Pediatrics, 2020)
Amount of parenchymal involvement in patients with interstitial pneumonia Covid-19 related, seems to be associated with worse prognosis. Nowadays 3D reconstruction imaging is expanding its role in clinical medicine. We aimed to use 3D lung reconstruction of a child with Covid-19 infection and interstitial pneumonia, to better visualize and quantitatively assess the percentage of parenchymal involvement. Volumetric Chest CT scan was performed in a 15 years old girl with interstitial lung pneumonia, Sars-CoV2 infection related. 3D modelling of the lungs, with differentiation of healthy and affected parenchymal area were obtained by using multiple software. 3D reconstruction imaging allowed us to obtain the quantification of the affected parenchymal areas in relation to the volumes of the entire lungs. Self-explaining 3D images, useful for the evaluation, study and for team discussion of the clinical case were also obtained. Quantitative Assessment of Parenchymal Involvement Using 3D Lung Model in Covid-19 Infection is feasible and it provides information which could play a role in the management and risk stratification of these patients.